2006
DOI: 10.1007/s10038-006-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence of the poor and ultrarapid metabolite alleles of CYP2D6, CYP2C9, CYP2C19, CYP3A4, and CYP3A5 in Taiwanese population

Abstract: Genetic polymorphisms of drug metabolizing enzymes, such as cytochromes P450 (CYPs), play major roles in the variations of drug responsiveness in human. The aim of this study is to identify the high prevalence (minor allele frequencies >1%) of the abnormal metabolite alleles of CYP2C9, CYP2C19, CYP2D6, CYP3A4, and CYP3A5 in the Taiwanese population. The genotyping of the functional single nucleotide polymorphisms (SNPs) of CYPs were conducted by direct exon sequencing in 180 Taiwanese volunteers. Twenty-one un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…The allele frequency of CYP2C19*2 in our study was in agreement with previous studies in Han Chinese (Chen et al, 2008), Japanese and African populations (Goldstein et al, 1997), but was significantly higher than that observed in Caucasians (Goldstein et al, 1997). Our result showed that the frequency of CYP2C19*3 was slightly lower than that in other Asian populations such as Taiwanese, Japanese or Korean (Roh et al, 1996;Goldstein et al, 1997;Liou et al, 2006); however, it was significantly higher than that in Caucasians and Africans (Goldstein et al, 1997). The CYP2C19*1/*2 and CYP2C19*1/*3, which indicate the intermediate metabolizer classification, accounted for about 41% (95% confidence interval: 0.35 ± 0.064) of CYP2C19 genotypes in the Mongolian population, which was similar to that in Mainland Han Chinese (Chen et al, 2008), but lower than that in Han Taiwanese (Liou et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The allele frequency of CYP2C19*2 in our study was in agreement with previous studies in Han Chinese (Chen et al, 2008), Japanese and African populations (Goldstein et al, 1997), but was significantly higher than that observed in Caucasians (Goldstein et al, 1997). Our result showed that the frequency of CYP2C19*3 was slightly lower than that in other Asian populations such as Taiwanese, Japanese or Korean (Roh et al, 1996;Goldstein et al, 1997;Liou et al, 2006); however, it was significantly higher than that in Caucasians and Africans (Goldstein et al, 1997). The CYP2C19*1/*2 and CYP2C19*1/*3, which indicate the intermediate metabolizer classification, accounted for about 41% (95% confidence interval: 0.35 ± 0.064) of CYP2C19 genotypes in the Mongolian population, which was similar to that in Mainland Han Chinese (Chen et al, 2008), but lower than that in Han Taiwanese (Liou et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Our result showed that the frequency of CYP2C19*3 was slightly lower than that in other Asian populations such as Taiwanese, Japanese or Korean (Roh et al, 1996;Goldstein et al, 1997;Liou et al, 2006); however, it was significantly higher than that in Caucasians and Africans (Goldstein et al, 1997). The CYP2C19*1/*2 and CYP2C19*1/*3, which indicate the intermediate metabolizer classification, accounted for about 41% (95% confidence interval: 0.35 ± 0.064) of CYP2C19 genotypes in the Mongolian population, which was similar to that in Mainland Han Chinese (Chen et al, 2008), but lower than that in Han Taiwanese (Liou et al, 2006). The frequency (8.0%) of poor metabolizer including CYP2C19*2/*2, CYP2C19*2/*3 and CYP2C19*3/*3 altogether in Chinese Mongolians was similar to other Asian populations but markedly higher than in Caucasians and Africans (2 to 7%; Bertilsson, 1995).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This mutation is mainly responsible for the high rate of poor metabolizers (PM) in Caucasians (5-9%), who are expected to be inefficient in metabolizing CYP2D6 substrates, such as risperidone and paroxetine ( Figures 5 and 6). Instead of CYP2D6*4, high frequencies of CYP2D6*10 (Dahl et al, 1995;Liou, Lin, Wu, & Wu, 2006;Wang, Huang, Lai, Liu, & Lai, 1993) and CYP2D6*17 (Leathart et al, 1998;Masimirembwa & Hasler, 1997) were found among those of East Asian and sub-Saharan African origins, respectively. Both of these alleles are associated with lower enzyme activities and slower metabolism of CYP2D6 substrates.…”
Section: Differences In Psychopharmacological Responses Across Ethnicmentioning
confidence: 89%
“…However, various 5-HT 3 receptor antagonists are not only metabolized by CYP2D6, but also metabolized via the CYP3A4 isoform. Furthermore, less than 2% of the Caucasian and Asian populations are categorized as ultrarapid metabolizers, with more than two active genes as a result of gene multiplication 10,13,14 . The clinical characteristrics of PONV are different from CINV.…”
mentioning
confidence: 99%